2009
DOI: 10.1002/jbm.a.32198
|View full text |Cite
|
Sign up to set email alerts
|

The application of type II collagen and chondroitin sulfate grafted PCL porous scaffold in cartilage tissue engineering

Abstract: This study investigates a poly(epsilon-caprolactone)-graft-type II collagen-graft-chondroitin sulfate (PCL-g-COL-g-CS) biomaterial as a scaffold for cartilage tissue engineering. Biodegradable polyester, PCL, was utilized to fabricate three-dimensional (3D) porous scaffolds by particulate leaching. The PCL scaffold was then surface modified by chemical bonding of 1,6-hexanediamine and the grafting of a bioactive polymer layer of COL and CS with the help of 1-ethyl-3-(3-dimethyl- aminopropyl) carbodiimide (EDC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(45 citation statements)
references
References 41 publications
0
44
1
Order By: Relevance
“…In addition to the pore structure design, a nanocomposite approach of using both organic matrix and inorganic nanocomponent can provide scaffolds that mimic native bone tissue composition (Chang et al 2010). Inorganic nanocomponents improve not only bone-bioactivity but also mechanical properties of polymeric matrices.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the pore structure design, a nanocomposite approach of using both organic matrix and inorganic nanocomponent can provide scaffolds that mimic native bone tissue composition (Chang et al 2010). Inorganic nanocomponents improve not only bone-bioactivity but also mechanical properties of polymeric matrices.…”
Section: Introductionmentioning
confidence: 99%
“…CHS stimulates the metabolic response of cartilage [390], possesses anti-inflammatory properties [391], and connects cells to extracellular matrix components [392]. CHS is extensively studied as a hydrogel for wound dressings and cartilage tissue engineering, [393] alone or in association with other biodegradable polymers [394,395]. For dental applications, Sawatjui et al fabricated a three-dimensional silk fibroin/gelatin-chondroitin sulfate-hyaluronic acid (SF-GCH) scaffold and showed that it promotes proliferation of mesenchymal stem cells by providing a supportive structure and the mimetic cartilage environment for chondrogenesis which enables cartilage regeneration [396].…”
Section: Proteins and Poly(amino Acids)mentioning
confidence: 99%
“…19 Polylactones or polycaprolactone (PCL) are two other widely studied synthetic polymers for cartilage repair. [20][21][22][23][24] PCL is a semicrystalline polymer with a glass transition temperature of about −60°C. The polymer has a low melting temperature (59°C-64°C) and is compatible with a range of other polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Blends with other polymers, block copolymers, and low-molecular weight polyols and macromers based on the caprolactone backbone are a few possible strategies. 24 However, these synthetic polymers, in the form they are used today, do not mimic the nanotopographical features that collagen and other extracellular matrix proteins create in cartilage tissue. In the pursuit of more "cell-friendly" polymeric surfaces, many physical and chemical methods have been developed to increase surface tension and surface roughness.…”
Section: Introductionmentioning
confidence: 99%